Lili Wu Chinese. (29th April 2022) - Shi, Menghui; Chen, Yiya
Abstract : Lili Wu Chinese ( ) is a Wu dialect ( ; ISO 639-3; code: wuu) spoken by approximately 38, 000 people who reside in the town of Lili ( ), one of the ten major towns in the Wujiang district ( ). The Wujiang district belongs to the prefectural-level municipality of Suzhou city ( ) in Jiangsu province ( ), the People's Republic of China. It is located at the juncture area of the city of Shanghai ( ), the city of Suzhou, and the city of Jiaxing ( ), as shown in Figure 1 .